2003
DOI: 10.1152/ajplung.00329.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain increases cell stiffness through cytoskeletal filament reorganization

Abstract: We tested the hypothesis that cytoskeletal reorganization induced by cyclic strain increases cytoskeletal stiffness (G′). G′ was measured by optical magnetic twisting cytometry in control cells and cells that had received mechanical strain for 10–12 days. G′ was measured before and after both contractile and relaxant agonists, and in the strained cells both parallel (Para) and perpendicular (Perp) to the aligned cytoskeleton. Before activation, G′ Para was 24 ± 5% (± SE) greater compared with Perp ( P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 28 publications
8
92
1
Order By: Relevance
“…Many families of CSK proteins contribute to overall cell stiffness, but F-actin tends to dominate in many cases (Pourati et al, 1998;Wu et al, 1998;Smith et al, 2003;Na et al, 2004;Huang et al, 2005) and thus was the focus herein. There is increasing information available on the elasticity of F-actin, including isolated filaments, networks having different degrees of crosslinks, and stress fibers (e.g., Liu and Pollack, 2002;Gardel et al, 2004;Deguchi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Many families of CSK proteins contribute to overall cell stiffness, but F-actin tends to dominate in many cases (Pourati et al, 1998;Wu et al, 1998;Smith et al, 2003;Na et al, 2004;Huang et al, 2005) and thus was the focus herein. There is increasing information available on the elasticity of F-actin, including isolated filaments, networks having different degrees of crosslinks, and stress fibers (e.g., Liu and Pollack, 2002;Gardel et al, 2004;Deguchi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This can be adapted for acute studies to enable simultaneous assessment of cell morphology and signal transduction events, such as intracellular Ca 2+ flux. Another widely used approach for acute studies is to use magnetic twisting cytometry to apply force and measure stiffness of the underlying cytoskeleton [230,231]. Twisting cytometry, atomic force microscopy and videomicroscopy are currently the most effective approaches with which to assess cell stiffness and shortening in cultured cells.…”
Section: Chronic Oscillatory Length Change In Cultured Asm Cellsmentioning
confidence: 99%
“…These changes depend on strain magnitude and orientation, as discussed in sections below. In several studies, SMITH and coworkers [230,[242][243][244] have demonstrated that a predominantly uniaxial (stretch in one direction) strain of ,10% applied for several days in culture increases proliferation, force generation, expression of contractile proteins, calcium sensitivity and cytoskeletal stiffness with contractile activation. Perhaps the most dramatic changes they have been shown are a doubling in shortening capacity and shortening velocity [245].…”
Section: Chronic Oscillatory Length Change In Cultured Asm Cellsmentioning
confidence: 99%
“…Force sensing, however, can also induce altered gene regulation [37], and the resulting adaptation processes can go on over the course of days and weeks. For instance, cyclic stretch applied to smooth muscle cells result over a time course of 10-12 days to an alignment of the cells perpendicular to the stretch direction and to an upregulation of contractile protein expression [13].…”
Section: Cytoskeletal Remodeling Dynamicsmentioning
confidence: 99%
“…Such a force balance need not be static in the sense that the degree of airway constriction reaches a steadystate, and indeed, over the past decade numerous experimental and theoretical studies have shown that airway caliber is equilibrated dynamically rather than statically [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Indeed, the force-length curve of activated smooth muscle is constantly changing as the muscle adapts to its mechanical surroundings, such as the length to which it is stretched or the load against which it must contract.…”
Section: Introductionmentioning
confidence: 99%